Effect of Solution Treatment on Microstructure and Properties of Al-20Si-1.5Mg Cast Aluminum Alloy. (July 2020) - Zhao, Gaozhan; Gao, Liqiang; Chen, Wen; Huang, Zhiwei; Xing, Zhihui; Chai, Shuxin
Abstract: The effects of the main process factors such as temperature and time on the microstructure and properties of hypereutectic Al-20Si-1.5Mg alloy were analyzed. The results show that when the solution treatment process is 510 °C × 6h, the primary silicon, eutectic silicon and Mg2 Si in the sample structure have been solution maximized, and the morphology distribution has been optimized, which is related to the passivation effect of solution treatment on silicon phase, etc.; At the same time, the hardness decreases first and then increases with the extension of solution time, and the inflection point appears at 6h. Compared with the as cast structure, the hardness is reduced by more than 15%. At this time, the super saturation of the alloy is the largest, which is conducive to obtain the best aging strengthening effect.